2023
DOI: 10.1186/s13677-023-00455-1
|View full text |Cite
|
Sign up to set email alerts
|

Managing the integration of teaching resources for college physical education using intelligent edge-cloud computing

Abstract: These days, colleges and universities have accumulated many resources in teaching and scientific research due to the acceleration of education information in China. However, many teaching resources are in short supply due to a lack of standardized resource construction and the closeness of management methods. Physical education significant teaching resources in Chinese colleges and universities must be utilized. If not integrated, it would seriously restrict the development of physical education in China. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…In the analysis of the results and findings from this journal article, the integration of the Internet of Things (IoT) in physical education is shown to have significant implications. Various studies, such as those described by Ding et al (2020), Che et al (2021), Hu et al (2021), Guo and Sun (2021), and Wang and Wang (2023), highlight various aspects of using IoT technologies in enhancing physical learning experiences, activity monitoring, classroom management, and teaching resource management. This integrated approach not only facilitates interactive learning but also assists in improving teaching efficiency and classroom management, as well as promoting innovation in curriculum and resource management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of the results and findings from this journal article, the integration of the Internet of Things (IoT) in physical education is shown to have significant implications. Various studies, such as those described by Ding et al (2020), Che et al (2021), Hu et al (2021), Guo and Sun (2021), and Wang and Wang (2023), highlight various aspects of using IoT technologies in enhancing physical learning experiences, activity monitoring, classroom management, and teaching resource management. This integrated approach not only facilitates interactive learning but also assists in improving teaching efficiency and classroom management, as well as promoting innovation in curriculum and resource management.…”
Section: Discussionmentioning
confidence: 99%
“…Through the collection and processing of field data, this research shows that the developed system has a positive effect on improving teaching and classroom management. Finally, the article by Wang and Wang (2023) proposed the integration and management of teaching resources for physical education in colleges using cloud computing and edge computing. This research highlights the importance of the management and integration of teaching resources in physical education in higher education.…”
Section: Cloudmentioning
confidence: 99%
“…In addition, studies have shown that physical education can also improve attention problems in children and adolescents [12]. With the acceleration of the educational information process, the management and integration of college sports resources through cloud computing can promote the mutual exchange of college resources and have practical significance for the development of college education [13]. Physical education runs through people's lives, so as to promote people's all-round development through high-quality physical education [14].…”
Section: Introductionmentioning
confidence: 99%
“…延 [11] 。云端也可利用用户的个性特征训练个性化模 型 [35] ,将训练好的模型传输给每个用户,用户在本 地直接进行推理。对于特定的用户端设备,云侧可 根据设备的存储空间选择合适的模型,采用模型压 缩等方法进一步减小网络传输的延迟,以改善用户 体验。随着联邦学习的发展和应用,用户可在不上 传自身数据的情况下更新云端模型,防止隐私泄露 和潜在的安全问题 [68,69] 中引入跨设备联邦学习 [7] ,以保护协同训练过程中 的隐私不被泄露,但在实施中需要在设备端部署 整个模型。随着深度学习方法的进步,VGG19 [72] 、 ResNet152 [73] 等视觉模型的参数越来越多,对设备 端的存储空间提出了更高要求,加大了协同训练难 度。为此,DC-CCL [62] 引入一种轻量级模型,基于 知识蒸馏方式模拟大型云端子模型;相应轻量级模 型可部署到移动设备上,用于控制小型子模型的优 化方向。DC-CCL 支持在移动设备上部署模型,规 避了存储空间不足的问题,仍可控制子模型的优化 方向。 (四)教育 近年来,智能校园成为应用热点,教育模式朝 着数字化、智能化方向转变,有望革新校园活动样 式 [74] 。端云协同技术为教育领域数字化、智能化发 展创造了机遇,丰富了典型的教育应用,如测验生 成、导学问答、非事实内容检测等。学生和教师可 以随时随地获取教材、课件、学习工具 [75] ,知识追…”
unclassified